Case report: ADULT syndrome: a rare case of congenital lacrimal duct abnormality - Zhou, Jichao; Wang, Yuchen; Zhang, Yinghong; You, Debo; Wang, Yi (Frontiers in Genetics, 2023)
Acro-dermato-ungual-lacrimal-tooth (ADULT) syndrome is a rare autosomal dominant inherited disease caused due to mutations in the TP63 gene. More commonly, mutations in the TP63 gene result in ectodermal dysplasia and/or orofacial cleft. ADULT syndrome is a type of ectoderm-related tissue dysplasia. This case report describes a patient with chronic tearing, congenital atresia, and obstruction of the lacrimal ducts, which are the main clinical manifestations of ADULT syndrome. This patient also presented with some clinical manifestations that were different from those of ADULT syndrome, namely, mild eyelid fusion and abnormal development of the fifth finger (a stiff fifth finger with camptodactyly that was shortened in length). The gene mutation in this patient was also at a site different from those usually reported in the literature. In this patient, c.518G > T resulted in p. G173V (accession number: NM_003722; exon4). We performed successful dacryocystorhinostomy and artificial lacrimal duct implantation.As shown above, we discussed the clinical characteristics and genetics of the disease in detail. In sharing this case, we aim to contribute to the current understanding of the genes and clinical manifestations of ADULT syndrome and to assist clinicians in the clinical diagnosis of TP63 mutation-related diseases.